SHIFTS IN VOTER BEHAVIOR AND THE ELECTORAL CHALLENGES FACING PKB IN THE 2024 DEMAK LOCAL ELECTION - Nina Sakinah; Supratiwi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Recent developments in Indonesia’s local democracy reveal a reconfiguration of voter behavior that challenges assumptions about the durability of identity-based electoral loyalty. This article analyzes the electoral defeat of the National Awakening Party (PKB) in the 2024 Demak local election as an empirical anomaly, given the party’s strong socio-religious embeddedness and its electoral dominance in the simultaneous legislative election within the same district. Rather than attributing the outcome solely to organizational weakness, the study situates PKB’s loss within broader shifts in voter rationality, the declining mobilizational capacity of religious identity, and structural constraints shaping local party performance. Employing a qualitative, narrative-based literature review, the article engages with scholarship on voting behavior, Islamic political mobilization, party institutional functions, and subnational democratic competition in Indonesia. The analysis demonstrates that voters increasingly evaluate candidates and parties through pragmatic, contextual, and performance-oriented considerations, thereby weakening the determinative role of Nahdlatul Ulama based identity appeals. Concurrently, deficiencies in candidate recruitment, limited campaign adaptability, and coordination challenges within broad electoral coalitions constrained PKB’s capacity to convert symbolic legitimacy and organizational networks into effective electoral support. This study contributes to the literature by demonstrating the declining electoral relevance of religious identity and emphasizing adaptive party organization in local Indonesian politics contemporary.